Proceso de atención de enfermería en paciente adulta mayor con cáncer uterino. - Carbo Navarrete, Stephany Corina (2022)
Uterine cancer is the most common cancer within a woman's reproductive system. It starts when healthy cells in the uterus change and grow out of control, forming a mass called a tumor. Uterine cancer includes 75% of all malignant neoplasms of the female genital tract and usually appears in women between 50 and 60 years of age. Cancer of the uterus or womb tends to have a higher incidence in women who have reached menopause. The most characteristic symptoms are bleeding, abnormal vaginal discharge, pelvic pain, and tenesmus. As with other types of cancer, the cause is unknown, but risk factors have been identified: menopause, promiscuity, sexually transmitted disease or family history, among others. The present clinical case was carried out with the main objective of applying the Nursing Care Process in an older adult patient diagnosed with uterine cancer and developing a standardized nursing care plan in which the main diagnoses, objectives and procedures are identified. interventions to be executed, where the assessment by domains, NANDA taxonomy, nursing diagnosis formulation and NIC, NOC care plan will be deployed. The result obtained was that with the correct, timely and effective application of the Nursing Care Process in an older adult patient with uterine cancer, optimal improvement and prevention of complications were achieved.